The Fungicide and Variety Integration Effect on Late Blight (Phytophthora infestans) Disease of Potato (Solanum tuberosum L.) in Western Amhara Region, Ethiopia - Asaye, Gebremariam; Abera, Merkuz; Tesfaye, Adane (International Journal of Sustainable Agricultural Research, 2019)
Potato is suffered by many abiotic and biotic factors. Among biotic factors late blight disease (LBD) is the most important. The study was conducted during 2017 at Adet and Debre-Tabor to determine and evaluate the combination effect of varieties and fungicides, to reduce LBD intensities and increase yield. Four potato varieties and three fungicides with untreated check were used in factorial randomized complete block design with three replications. Lowest disease severity 11.11% was obtained from Belete and Gudene at Adet and Belete at Debre-Tabor. Similarly, the lowest AUDPC (9.33 and 89.83 %-days) were expressed from Gudene + Saboxyl 72% at Adet and Debre-Tabor, respectively, whereas, the maximum PSI and AUDPC were obtained from untreated plots. In average up to 359.81% yield increases were recorded from Abalo + Saboxyl 72% WP. The highest marginal rates of return (2,886.50 % and 3,786.35%) were obtained from Saboxyl 72% treated plots of Abalo & Guassa at Debre-Tabor and Adet, respectively. Therefore, an application of Saboxyl 72% with different varieties was effective at both locations to reduce the yield loss of potato and could be recommended to manage LBD. The combination of Saboxyl 72% with Gudene, Belete and Guassa were highly hinder LBD development at both locations. Even though, its yielding capacity was relatively lower Gudene could be recommended for production without fungicide. Variety Belete and Guassa could be recommended for production in combination with Saboxyl 72%, since they have best performance with relatively lower disease reaction at Adet and Debre-Tabor, respectively.